PERILAKU CYBERSEX DI MEDIA SOSIAL FACEBOOK (Analisis Wacana pada Akun Grup “Cerita Bikin Basah”) - Makaria Asriana Hadia; Hotlif A. Nope; Susana C. L. Pellu (Jurnal Pluralis, 2023)
Social Media is online or online media that is used as a means of social interaction on the internet. The positive impact of using social media is that people can easily carry out activities on social media, such as communicating or interacting to providing information or content in the form of photo and video writing, along with increasing use of social media there are also negative impacts, one of which is cybersex. Cybersex is anything posted on social media, be it in the form of writing, pictures, videos, or statuses that mix sexually. The formulation of the problem in this research is what is the meaning of the language of status updates for group members